Mechanisms and Conditions that Affect Phase Inversion Processes. The Case of High‐Impact Polystyrene. Issue 3 (3rd December 2019) - Maffi, Juan M.; Casis, Natalia; Acuña, Pablo; Morales, Graciela; Estenoz, Diana A.
Abstract : The phase inversion (PI) during the bulk polymerization of the styrene–polybutadiene system (high impact polystyrene manufacturing process) is empirically and theoretically studied in this article. In the experimental work, a series of reactions were performed with benzoyl peroxide as initiator and at temperatures considered of industrial interest (80°C and 90°C), varying also the reactor stirring level. PI was determined by offline viscosity measurements and verified by scanning transmission electron microscopy. The rheological behavior of each reacting system was analyzed and an empirical correlation to predict its apparent viscosity from fundamental reaction parameters was derived. This was achieved successfully for both before and after the PI point. POLYM. ENG. SCI., 60:491–502, 2020. © 2019 Society of Plastics Engineers